THE EFFECTIVENESS OF PAIRS CHECK MODEL WITH A SCIENTIFIC APPROACH TO STUDENTS' LEARNING RESULTS - Halidin, Halidin; La Ode, Sirad; Marniati, Marniati (IJBLE Scientific Publications Community Inc., 2023)
This research aims to determine the efficiency of the Pairs Check learning model with a scientific approach to students' mathematics learning results. The data on students' mathematics learning outcomes were acquired using the instrument at posttest. Descriptive statistics and inferential statistics were employed in the data analysis approach. The descriptive study found that the mathematics learning outcomes of 30 students taught using Pairs Check model using a scientific approach had an average value (mean) of 80,533. While the students who were taught using conventional learning consisting of 30 students showed an average score is 76,333. Consequently, it can be argued that learning mathematics using a pair check learning model with a scientific approach is more effective than conventional learning methods.